Miniature rectangular ring band-pass filter with embedded Barium Strontium Titanate capacitors - Osman, Nurul Huda; Free, C. (IEEE (IEEE Xplore), 2014)
The design of a miniature band-pass filter, using a ring resonator is presented in this paper. The miniaturization is achieved through the use of embedded parallel plate capacitor, implemented using Barium Strontium Titanate (BST) thick film paste. Measured data on filter response and loss at X—band are presented. Results show good response and low insertion loss.